Migrants and proletarians : urban labour in the economic development of Uganda - Elkan, Walter (London ; New York : Published on behalf of the East African Institute of Social Research by Oxford University Press, 1960)
Labour in economic development conjures up for many an image of peasants streaming from the countryside to towns, to man new factories and to start a new life. Economies develop in diverse ways, and this book is an attempt to show how in one country, Uganda in East Africa, a very different pattern has emerged, in which there is a perpetual flow between town and country and in which, although the towns are growing, there are few signs of the growth of an urban working class.
Bibliography: p. [142]-145.
rpm 20/02/2018
Loans
Keywords: Labor and laboring classes